Eolian sedimentation in central European Auel dry maar from 60 to 13 ka. (May 2021) - Fuhrmann, Florian; Seelos, Klemens; Sirocko, Frank
Abstract: The climate in central Europe during the last 60 ka is characterized by rapid temperature and moisture changes and strong cold periods (Heinrich events). All these variations are preserved in sediments of marine and also some terrestrial archives. Here we present a continuous, terrestrial sediment record with almost all Greenland stadials and Heinrich events between 60 and 13 ka visible from carbonate roundness of the Eifel Laminated Sediment Archive Dust Stack-20 and CaCO3 data for central Europe. The carbonate roundness data show almost all stadials between 60 and 13 ka. CaCO3 data show a general transport system change with the beginning of Heinrich event 3. Since there are no carbonates west of the Auel Maar, we conclude that the eolian-transported grains were not transported by westerly but easterly winds. These postulated easterly winds during the last glacial maximum are supported by similar findings of previous works.